Classification of epileptic EEG signals using sparse spectrum based empirical wavelet transform. Issue 25 (8th October 2020) - Nishad, A.; Upadhyay, A.; Ravi Shankar Reddy, G.; Bajaj, V.
Abstract : The unnatural activities of brain due to seizure events are analysed by electroencephalogram (EEG) signals which are captured from the brain. In this work, a methodology is proposed to classify the seizure EEG signals. In the proposed method, a novel sparse spectrum based empirical wavelet transform (SS‐EWT) is applied to decompose the EEG signal into coefficients. From the obtained SS‐EWT coefficients, the cross‐information potential and normalised energy are extracted as features. Then these features are ranked using the RELIEFF method to obtain significant features. After ranking, these features are fed into the k ‐nearest neighbour ( k ‐NN) classifier to classify EEG signals corresponding to different brain activities. In this work, the first classification problem is the classification of the seizure (S), seizure‐free (F), and normal (Z) EEG signals in which obtained classification accuracy (Acc) is 96.67 % . The second classification problem is the classification of S and Z EEG signals in which 100 % Acc is achieved by the proposed method.